РОЛЬ МЕДИЦИНСКИХ ФРАЗЕОЛОГИЗМОВ В ПОСТРОЕНИИ РЕКЛАМНОГО ТЕКСТА - Гафуров, Б.З. (SCIENCE and SOCIETY, 2021)
This article discusses the specifics of the functions of advertising texts, which are formed using phraseological phrases. Examples are given, and the scope of their use is described.
Keywords: advertising; phraseological turnover; text; function; scope of use; meaning